Optimization of cultural parameters for pectin methylestrase and polygalacturonase production from Schizophyllum commune in solid state fermentation (Bangladesh Journal of Botany, 2019)
The aim of this study was optimization of pectinolytic enzymes i.e. pectin methylesterase and polygalacturonase from Schizophyllum commune using the mosambi peels as substrate in a solid state fermentation process. Results revealed that maximum pectin methylesterase activity of 394.82 U/ml was observed at pH 6, temperature 35°C, time period of 3 days, substrate concentration of 3 g and 3 ml inoculum size. While polygalacturonase showed maximum activity of 381.69 U/ml at pH 4, temperature 45°C, time period of 1 day, substrate concentration 25 g and 5 ml inoculum size. Statistical analysis revealed that the proposed model was found very significant as indicated by p-values.